Tenure and experience effects on wages: A theory - Ken Burdett; Melvyn Coles (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper investigates equilibria in a labor market where firms post wage/tenure contracts and risk-averse workers, both employed and unemployed, search for better paid job opportunities. Different firms typically offer different contracts. Workers accumulate general human capital through learning-by-doing. With on-the-job search, a worker's wage evolves endogenously over time through experience effects, tenure effects and quits to better paid employment. This equilibrium approach suggests how to identify econometrically between experience and tenure effects on worker wages.
Keywords: J41; 330; experience; tenure; search; equilibrium; Lohntheorie; Berufserfahrung; Betriebszugehörigkeit; Arbeitsuche; Arbeitsangebot; Arbeitsmarkttheorie; Theorie